Nali’s age in the Mastura pome - پرۆفیسۆر دکتۆر سەردار ئەحمەد گەردى (QALAAI ZANIST JOURNAL, 2021)
Nali birth and death dates are not defined yet, each schooler is appointing these dates according to their own researchers. Same as his life, his age when he wrote the Mastura pome is not defined, some say he was a teenager, some say he was a grown young man another group agrees that he was an old man when he wrote the pome. The objective of these paper is to identify his age stylistic analysis method and answering all the claims which there are about Nali’s age when he wrote the pome. The research consists of an introduction and some axes : The first axis is the peot’s sociology. Second: a research on the ages claimed for Nali when he wrote the pome. The third axis is Nali’s poetic background or experience, in this part, some questions have been raised such as: can this masterpiece belongs to a teenager? Or it comes from deep experience? The forth part is a research on the time and place of the pome. The fifth part is on the content and form of pome and how these are related to Nali’s age according to Bozeman’s formula. The research raises many questions in different areas which answering them will clarify many hidden aspects of Nali’s life and the time the pome was written.from URL.